A SYSTEMATIC REVIEW ON THE IMPLEMENTATION OF LEAN HOSPITAL TO IMPROVE CHEMOTHERAPY UNIT SERVICES IN HOSPITAL - Tambunan, Evelyn Hemme (Nurse and Holistic Care, 2025)
Background: Rising demand for efficient chemotherapy services calls for improved hospital processes. Lean Hospital applies Lean principles to reduce waste and enhance service quality. Objective: This study aims to assess the available quantitative evidence regarding the impact of lean methodologies on key performance indicators (KPIs) such as cost efficiency, service quality, and patient satisfaction in the chemotherapy unit. Design: A systematic literature review methodology was adopted to collate evidence related to the implementation of lean hospital practices in chemotherapy units using PRISMA guidelines for Scopus, Web of Science, and PubMed searches. Data Sources: This systematic review synthesizes peer-reviewed studies published between 2015 and 2023, retrieved from Scopus, Web of Science, and PubMed databases. Review Methods: A systematic literature search was conducted in Scopus, Web of Science, and PubMed using a combination of keywords and MeSH terms related to lean hospital practices and chemotherapy services. Boolean operators and truncation were applied to refine results, with the search limited to peer-reviewed articles published between 2015 and 2023. Title, abstract, and full-text screenings were conducted based on predefined inclusion criteria. Results: This study included a total of 48 full-text studies for analysis. The findings indicate statistically significant improvements in process efficiency and service quality metrics following lean interventions, with cost savings ranging from 10% to 35% observed across studies. Conclusion: This systematic review shows that Lean Hospital practices effectively improve chemotherapy unit services. Lean interventions significantly reduce costs, enhance service quality, and boost patient satisfaction. Despite some methodological variations, the evidence supports lean methods as a cost-effective strategy for optimizing care delivery.